FEM Model of Structure for Weightlifting in CrossFit in Terms of Material Parameters - Soukup, Josef; Krmela, Jan; Krmelová, Vladimíra; Skočilasová, Blanka; Artyukhov, Artem (My University, 2019)
The article deals with problem of construction for Weightlifting in CrossFit from point of view of material parameters. The structure must withstand repeated impact loads. Therefore it is necessary to deal with stress-strain states also. Because of behavior of impact loading and elastomers used in FEM computational model, explicit integration scheme and material constitutive models must be included. To use constitutive models, material parameters must be well known. That is the reason, why this article is oriented to obtaining material parameters of elastomers for FEM computational modeling based on their hardness. For create a 3D model the SolidWorks software is used and for FEM analyses well-known the ANSYS Workbench software is used.
MKP model konstrukce pro vzpěračské účely v crossfitu z hlediska vstupních parametrů
Keywords: CrossFit; FEM; material parameters; elastomer; hardness; crossfit; MKP; materiálové parametry; elastomer; tvrdost